Strengthening the Protection of Children in Adhesion Daycare Contracts Through the Integration of Duty of Care and Vicarious Liability - Suratman Suratman; Lestari Anggraini Lestari Anggraini; Niza Wibyana Tito Niza Wibyana Tito; Happy Brilliant Srikandy Happy Brilliant Srikandy; Firdaus Akhirus Zamansyah Firdaus Akhirus Zamansyah; Noor Rohmat Noor Rohmat (Universitas Mataram, 2026)
The phenomenon of violence against children in daycare Little Aresha Yogyakarta shows the systemic weakness in child protection that stems from the fragility of legal construction in child care cooperation agreements. Custody agreements that have been used tend to be administrative and have not been able to provide adequate legal protection for parents and children as recipients of services. This study uses normative legal research methods with a case study approach to analyze the weaknesses of conventional daycare contracts, particularly related to operational legality, division of responsibilities, and consumer protection of child care services. The results showed that conventional daycare contracts are still asymmetric and do not accommodate the principle of comprehensive legal protection. The integration of the doctrine of Duty of Care and Vicarious Liability into the clauses of the agreement is considered to be able to strengthen the legal responsibility of daycare managers for the actions and omissions of caregivers. The reconstruction of the contract is carried out through the establishment of an operational permit as a condition for the validity of the agreement, setting standards for the ratio of companions and children, the obligation to certify staff competence, and strengthening supervision mechanisms. Digital transparency through real-time CCTV access is also placed as a contractual right of parents to prevent violence and create parenting accountability. The proactive-protective contract Model is ideally able to create a more fair, transparent, and accountable legal relationship, while strengthening the position of parents as consumers of child care services through the civil liability mechanism of daycare managers.